2012
DOI: 10.1080/01431161.2011.640959
|View full text |Cite
|
Sign up to set email alerts
|

Validation of satellite-derived tropical cyclone heat potential with in situ observations in the North Indian Ocean

Abstract: Tropical cyclone heat potential (TCHP) is an important ocean parameter influencing cyclones and hurricanes. The best approach for computing TCHP is to use in situ measurements. However, since in situ data have both spatial and temporal limitations, there is a need for satellite-based estimations. One potential solution is to use sea surface height anomalies (SSHAs) from altimeter observations. However, any estimation derived from satellite measurements requires extensive regional validation. In this letter, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…The comparison between in situ and satellite‐derived TCHP shows a bias ( in situ values being on the higher side) of 8.9 kJ cm −2 with a coefficient of determination, R 2 , of 0.82 and root mean square error (RMSE) of 9.4 kJ cm −2 (Figure ). Nagamani et al () compared the two estimations over the entire north Indian Ocean (NIO) and found an RMSE of 20.95 kJ cm −2 with an R 2 of 0.65 and bias of 11.27 kJ cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…The comparison between in situ and satellite‐derived TCHP shows a bias ( in situ values being on the higher side) of 8.9 kJ cm −2 with a coefficient of determination, R 2 , of 0.82 and root mean square error (RMSE) of 9.4 kJ cm −2 (Figure ). Nagamani et al () compared the two estimations over the entire north Indian Ocean (NIO) and found an RMSE of 20.95 kJ cm −2 with an R 2 of 0.65 and bias of 11.27 kJ cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the estimation of TCHP from altimeter observations and its validation with in situ measurements over the north Indian Ocean during 1993–2009 is given by Nagamani et al . (). As the TCHP derived from the satellite altimeter data is limited to recent years (1993–2011), we have also used the TCHP derived from the inter‐annual three monthly mean temperature profiles (using the Equation ) of the World Ocean Atlas (WOA), which is available for the period of 1955–2011 at http://www.nodc.noaa.gov/OC5/3M_HEAT_CONTENT/anomaly_data.html.…”
Section: Methodsmentioning
confidence: 97%
“…In the Bay of Bengal, for example, where river water can persist in the near surface layer, salinity can have a dominant role in determining the subsurface density structure and the SSH (e.g., Yu and McPhaden, 2011); this can have a detrimental effect on the TCHP derived from satellite observations. Nevertheless, comparison of TCHP values derived from satellites and in situ observations in the Bay of Bengal has shown that satellite-derived estimates are generally unbiased, and estimates with a precision better than 20 kJ cm −2 are often obtained (Nagamani et al, 2012).…”
Section: Ocean Observationsmentioning
confidence: 99%